Local Production of Activated Factor X in Atherosclerotic Plaque Induced Vascular Smooth Muscle Cell Senescence. Issue 1 (December 2017) - Sanada, Fumihiro; Muratsu, Jun; Otsu, Rei; Shimizu, Hideo; Koibuchi, Nobutaka; Uchida, Kazutaka; Taniyama, Yoshiaki; Yoshimura, Shinichi; Rakugi, Hiromi; Morishita, Ryuichi
Abstract Our previous study demonstrated that coagulation factor Xa (FXa) induced endothelial cell senescence, resulting in inflammation and impaired angiogenesis. This mechanism is dictated through protease-activated receptors, PARs, insulin-like growth factor-binding protein 5 (IGFBP-5), and p53. Activation of PARs contributes to the pathophysiology of several chronic inflammatory diseases, including atherosclerosis. Thus, we speculated that similar mechanism might participate in the progression of atherosclerotic plaques. In the present study, we successfully identified the cells that produced FX/Xa in atherosclerosis using human atherosclerotic plaques obtained from carotid endarterectomy.In situ hybridization for FX revealed that FX was generated in vascular smooth muscle cells (VSMC), inflammatory cells, and endothelial cells. Then, we examined the effects of FXa on the growth of VSMCin vitro . The present study revealed that chronic FXa stimulation significantly induced the senescence of VSMC with concomitant upregulation of IGFBP-5 and p53. Inhibition of FXa signaling with rivaroxaban or knock down of IGFBP-5 significantly reduced FXa-induced VSMC senescence and inflammatory cytokine production. Finally, we confirmed that FXa and IGFBP-5 are co-distributed in atherosclerotic plaques. In conclusion, induction of senescence of VSMC induced by locally produced FX/Xa may contribute to the progression of atherosclerosis.